Pengaruh Capital Intensity, Inventory Intensity, Profitabilitas, dan Leverage Terhadap Agresivitas Pajak - Kadek Diviariesty; Ni Kadek Ayu Mitha Cahyani (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2024)
This study aims to determine the effect of Capital Intensity, Inventory Intensity, Profitability and Leverage on Tax Aggressiveness in Basic Industry and Chemical Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The total number of research samples was 132 companies were obtained that met the requirements in this study. The main theory used in this study is agency theory and stakeholders. The data analysis technique used in this study is Multiple Linear Regression Analysis. The results of this research are that the inventory intensity and leverage variables have no effect on corporate tax aggressiveness. Meanwhile, the capital intensity and profitability variables have a significant negative effect on corporate tax aggressiveness. Profitability is proxied using the Return on Assets (ROA) formula, leverage is proxied using the Debt to Total Assets Ratio (DAR) formula and tax aggressiveness is proxied using the Effective Tax Rate (ETR).